Quality of life in systemic lupus erythematosus: description in a cohort of French patients and association with blood hydroxychloroquine levels. (June 2016) - Jolly, M; Galicier, L; Aumaître, O; Francès, C; Le Guern, V; Lioté, F; Smail, A; Limal, N; Perard, L; Desmurs-Clavel, H; Boutin, D L T H; Asli, B; et al.
Objectives: Benefits of hydroxychloroquine (HCQ) use on physician reported outcomes are well documented in systemic lupus erythematosus (SLE). We assess for the first time the association and predictive value of blood HCQ levels towards health-related quality of life (HRQOL) in SLE. Methods: Data from the PLUS study (a randomized, double-blind, placebo-controlled, multicentre study) were utilized. Blood HCQ levels were quantified by high-performance liquid chromatography along with HRQOL assessments (Medical Outcomes Study-SF-36) at baseline (V1) and month 7 (V2). Results: 166 SLE patients' data were analysed. Mean (SD) age and disease duration were 44.4 (10.7) and 9.3 (6.8) years. Eighty-seven per cent were women. Mean (SD, median, IQR) HCQ concentrations in the blood at V1 were 660 (314, 615, 424) ng/ml and increased to 1020 (632, 906, 781) ng/ml at V2 (mean difference 366 units, 95% confidence interval −472 to −260, p < 0.001). No significant correlations between HCQ concentrations with HRQOL domains at V1 or V2 were noted. There were no differences in HRQOL stratified by HCQ concentrations. HCQ concentrations at V1 or changes in HCQ concentration (V2-V1) were not predictive of HRQOL at V2 or changes in HRQOL (V2-V1). Conclusions: No association of HCQ concentrations with current or longitudinal HRQOL were found in SLE.